Zirconia as A Core Material - A Literature Review - DEVI, SANJANA; ARIGA, PADMA; TULSANI, MINAL; RUPAWAT, DIVYA (The journal of contemporary issues in business and government, 2020)
Teeth that have become severely compromised by decay, large failing restorations, or fracture most often require full-coverage crowns to restore them to their original form and function. A core buildup is a restoration placed in a badly broken down or grossly decayed tooth to restore the bulk of the coronal portion of the tooth. This facilitates the subsequent restoration by means of an indirect extra coronal restoration. The strength of the tooth can be enhanced with intracoronal support. It should have compressive strength to resist intraoral forces and flexural strength to prevent core dislodgement during function. It should also have sufficient flexural strength, biocompatibility, resistance to leakage of oral fluids at the core-tooth interface, ease of manipulation, and ability to bond to remaining tooth structure. The primary purpose of a core build- up is to replace enough missing tooth structure to permit the creation of ideal retention and resistance form in the crown preparation. Materials used for core restoration after endodontic treatment include amalgam, resin composites, zirconia to name a few. The aim of this review is to evaluate the use of zirconia as a core material by assessing the studies available in comparison to other core materials.